2015
DOI: 10.15436/2376-0949.15.031
|View full text |Cite
|
Sign up to set email alerts
|

Composition Diversity and Abundance of Gut Microbiome in Prediabetes and Type 2 Diabetes

Abstract: Association between type 2 diabetes (T2DM) and compositional changes in the gut micro biota is established, however little is known about the dysbiosis in early stages of Prediabetes (preDM). The purpose of this investigation is to elucidate the characteristics of the gut micro biome in preDM and T2DM, compared to Non-Diabetic (nonDM) subjects. Forty nine subjects were recruited for this study, 15 nonDM, 20 preDM and 14 T2DM. Bacterial community composition and diversity were investigated in fecal DNA samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
81
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(97 citation statements)
references
References 38 publications
14
81
1
1
Order By: Relevance
“…First, α-diversity was higher in cases. This finding contrasts with few early reports in T2D where α-diversity is often decreased (Larsen et al, 2010;Lambeth et al, 2015;Dominguez-Bello et al, 2019). This observation may be due to treatment and/or lifestyle changes (e.g., diet, physical activity) that are prescribed following diabetes diagnosis as supported by our analyses that treatment may contribute to increased α-diversity.…”
Section: Discussioncontrasting
confidence: 98%
“…First, α-diversity was higher in cases. This finding contrasts with few early reports in T2D where α-diversity is often decreased (Larsen et al, 2010;Lambeth et al, 2015;Dominguez-Bello et al, 2019). This observation may be due to treatment and/or lifestyle changes (e.g., diet, physical activity) that are prescribed following diabetes diagnosis as supported by our analyses that treatment may contribute to increased α-diversity.…”
Section: Discussioncontrasting
confidence: 98%
“…Similarly, previous studies examining the relation of Shannon Index with CVD risk factors have generally showed null results. 33, 34 These data suggest that the abundance of distinct microbial taxa may be more important than their relative frequency in determining CVD risk.…”
Section: Discussionmentioning
confidence: 90%
“…The abundance of the genus Roseburia was negatively correlated with the plasma glucose levels in a human study [56], and the depletion of the genus Roseburia is a characteristic feature of the microbiome in type 2 diabetic patients [57]. In addition, a high abundance of the genus Collinsella is a characteristic feature of the microbiome in type 2 diabetic patients [58], and a structured weight loss program reduced the abundance of the genus Collinsella in obese type 2 diabetic patients [59]. Based on these insights, the alterations in the abundances of Roseburia and Collinsella observed in our study could have affected obesity in these patients.…”
Section: Discussionmentioning
confidence: 98%